(3GdJhLjg TQM GdeZfj eNJUQ GdJfHjgs - (3HQgGf GdOjf EHQGgje Hf ehSi GdEHfGSjs; (3CHh GdbGSe,J (B738 (3g` s
(3ChdgG (B:s
(3GeG HYO aEf cJGH GdeZfj eNJUQ ddTjN GdYdGeI CHj GdbGSe TQa GdOjf GdHGQRi GdMehj eSJeOkG ef TQMg GdcaGjI s
(3BNQgG (B:s
(3aaj hLhH YJbg hLgGf hGddg CYde s
(3GdeZfi eNJUQ GdJfHjg GfXQ cTa GdXfhf L (B1 (3U` (B492s
(3GdfSNI HgG MhGTs
(3fSNI KGfjIs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3JHUQGJ GdCUd (B:s
Keywords: (3Gdabg GdTGaYjs